Negative electrode for secondary battery with improved rapid charging performance, manufactruing method thereof and secondary battery comprising the negative electrode
Patent Information
- Application Number
- KR1020250000161
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2045-01-02
Smart Images

Figure 112025000181483-PAT00002_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a negative electrode for a secondary battery with improved rapid charging performance, a method for manufacturing the same, and a secondary battery comprising the negative electrode. Background Technology
[0003] Recently, lithium-ion batteries are being widely applied not only to small devices such as portable electronic devices, but also to medium and large devices such as battery packs or power storage devices for hybrid or electric vehicles. In particular, with the recent increase in interest in environmental issues, a lot of research is being conducted on electric vehicles and hybrid electric vehicles that can replace fossil fuel-using vehicles, such as gasoline and diesel vehicles, which are one of the main causes of air pollution.
[0004] Due to limitations in energy density, conventional lithium-ion batteries are limited to applications such as short-distance electric vehicles. Consequently, technology development to date has focused intensively on increasing the energy density of lithium-ion batteries.
[0005] However, developed automotive lithium-ion batteries have the problem of requiring a long time to recharge after discharge during vehicle operation. Consequently, as the adoption rate of electric vehicles increases, there is a growing demand to reduce charging times to a level acceptable to users. Furthermore, electric vehicles must be able to operate without issues even in situations requiring high power output, such as rapid acceleration. This requires high-rate discharge performance for lithium-ion batteries, but currently, there is no technology available to meet this requirement.
[0006] Meanwhile, a lithium secondary battery is a rechargeable power generation device composed of a stacked structure of a positive electrode, a separator, and a negative electrode. During charging, a lithium extraction reaction occurs in the positive electrode, where lithium contained in the positive electrode active material is oxidized and released, while a lithium insertion reaction occurs in the negative electrode, where lithium is reduced and enters the negative electrode active material. Generally, since the extraction reaction in the positive electrode active material is faster than the insertion reaction in the negative electrode active material, the rapid charge / discharge performance of a lithium secondary battery is primarily determined by the negative electrode.
[0007] In reality, materials containing graphite are widely used as the negative electrode active material of the above-mentioned negative electrode. The average potential when the graphite-containing material releases lithium is approximately 0.2V (Li / Li + (Based on) and exhibits a relatively flat discharge potential. For this reason, when graphite is used as a negative electrode active material, the voltage of the secondary battery is high and constant, which is an advantage. However, the electrical capacity per unit mass of graphite material is small at 372 mAh / g. On the other hand, since the capacity of current graphite materials has been improved to be close to the theoretical capacity mentioned above, it is difficult to further increase the capacity. In addition, when graphite is used as a negative electrode active material, the lithium ion insertion reaction proceeds at a slow rate, so there is a limitation in that the rapid charging performance is low compared to cases where other negative electrode active materials are applied.
[0008] Therefore, in order to fundamentally resolve these problems, there is a high need for technology capable of realizing not only high-capacity characteristics but also rapid charging characteristics for secondary batteries. Prior art literature
[0010] Korean Patent Publication No. 2024-0084705 The problem to be solved
[0011] The objective of the present invention is to provide a negative electrode for a secondary battery with improved rapid charging performance, a method for manufacturing the same, and a secondary battery comprising the negative electrode. means of solving the problem
[0013] In order to solve the above-described problem, in one embodiment, a method for manufacturing a negative electrode for a secondary battery according to the present invention comprises the steps of: applying a negative electrode slurry having a viscosity of 5,500 cp to 12,000 cp and a solid content of 51 wt% to 55 wt% onto a current collector; applying a magnetic field to the applied negative electrode slurry; drying; and rolling.
[0014] In addition, the negative electrode active material layer formed through the above rolling step has an orientation index (OI) according to Formula 1 below in the range of 1 to 10.
[0015] [Equation 1]
[0016] OI = I 004 / I 110
[0017] In the above Equation 1,
[0018] I 004 represents the area of the peak indicating the (0,0,4) crystal plane of the carbon-based active material during X-ray diffraction (XRD) spectroscopic analysis of the cathode active material layer, and
[0019] I 110 represents the area of the peak indicating the (1,1,0) crystal plane of the carbon-based active material during X-ray diffraction (XRD) spectroscopic analysis of the cathode active material layer.
[0020] The above cathode slurry includes a carbon material as a cathode active material. Specifically, the above cathode slurry includes one or more carbon materials selected from artificial graphite and natural graphite as a cathode active material. In one embodiment, the above cathode slurry includes natural graphite (GN) and artificial graphite (GA) as cathode active materials in a weight ratio of 60:40 to 40:60 (GA:GN).
[0021] Specifically, the cathode slurry may further include a silicon-based cathode active material. In one example, the content of the silicon-based cathode active material is in the range of 0.1 weight% to 30 weight% based on the total weight of the cathode active material contained in the cathode slurry.
[0022] The above silicon-based negative electrode active material is silicon (Si), silicon carbide (SiC), a composite of carbon and silicon (Si / C), and silicon oxide (SiO₂). q ..., provided that it includes at least one of 0.8≤q≤2.5).
[0023] The orientation index (OI) of the cathode slurry that has undergone the step of applying the magnetic field is in the range of 0.1 to 5. The orientation index (OI) of the cathode slurry can be calculated in accordance with Equation 1.
[0024] In the step of applying the magnetic field, the strength of the applied magnetic field is in the range of 2,000G to 12,000G. Specifically, in the step of applying the magnetic field, the strength of the applied magnetic field is in the range of 3,500G to 9,500G. The time for applying the magnetic field can be controlled in the range of 1 second to 30 seconds.
[0025] The porosity (%) of the cathode active material layer that has undergone the above rolling step is in the range of 25% to 35%.
[0026] In another embodiment, the method for manufacturing a negative electrode for a secondary battery according to the present invention repeats the steps of applying a negative electrode slurry onto a current collector, applying a magnetic field, and drying twice. Specifically, in the first process cycle, a negative electrode slurry is applied to the top surface, which is one side of the current collector, to form a first negative electrode active material layer. Then, in the second process cycle, a negative electrode slurry is applied to the back surface, which is the opposite side of the current collector, to form a second negative electrode active material layer.
[0027] In one example, in the first process cycle, the strength of the magnetic field applied during the step of applying the magnetic field is in the range of 2,000G to 9,000G. Additionally, in the second process cycle, the strength of the magnetic field applied during the step of applying the magnetic field is in the range of 2,500G to 9,500G. The time for applying the magnetic field can be controlled in the range of 1 second to 30 seconds, 2 seconds to 20 seconds, or 3 seconds to 10 seconds.
[0028] In another example, the difference in the average orientation index (OI) of the first and second cathode active material layers is 1.5 or less.
[0030] In addition, the present invention provides a negative electrode for a secondary battery manufactured through the manufacturing method described above. In one example, the negative electrode for a secondary battery according to the present invention comprises a current collector; and a negative electrode active material layer formed on one or both sides of the current collector. In addition, the negative electrode active material layer has an orientation index (OI) according to Formula 1 below in the range of 1 to 10.
[0031] [Equation 1]
[0032] OI = I 004 / I 110
[0033] In the above Equation 1,
[0034] I 004 represents the area of the peak indicating the (0,0,4) crystal plane of the carbon-based active material during X-ray diffraction (XRD) spectroscopic analysis of the cathode active material layer, and
[0035] I 110 represents the area of the peak indicating the (1,1,0) crystal plane of the carbon-based active material during X-ray diffraction (XRD) spectroscopic analysis of the cathode active material layer.
[0036] The above-described cathode active material layer includes a carbon material as the cathode active material. Specifically, the above-described cathode active material layer includes one or more carbon materials selected from artificial graphite and natural graphite as the cathode active material. In one embodiment, the above-described cathode active material layer includes natural graphite (GN) and artificial graphite (GA) as the cathode active material in a weight ratio of 60:40 to 40:60 (GA:GN).
[0037] In another example, a negative electrode for a secondary battery according to the present invention comprises a current collector; a first negative active material layer formed on one side of the current collector; and a second negative active material layer formed on the opposite side of the current collector. In addition, the difference in the average orientation index (OI) between the first and second negative active material layers is 1.5 or less.
[0039] In addition, the present invention provides a secondary battery comprising the negative electrode described above. In one embodiment, the secondary battery has a structure comprising an electrode assembly having a structure in which a negative electrode, a positive electrode, and a separator are located between the negative electrode and the positive electrode.
[0040] As an example, the anode comprises an anode active material layer formed on an anode current collector. The anode active material layer comprises one or more of the particulate active materials represented by the following chemical formulas 1 and 2 as the anode active material.
[0041] [Chemical Formula 1]
[0042] Li x [Ni y Co z Mn w M 1 v ]O2
[0043] [Chemical Formula 2]
[0044] LiMn p M 2 1-p O4
[0045] In the above Chemical Formulas 1 and 2,
[0046] M 1It is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0047] x, y, z, w, and v are 1.0≤x≤1.30, 0.5≤y<1, 0, respectively. <z≤0.3, 0<w≤0.3, 0≤v≤0.1이되, y+z+w+v=1이고,
[0048] M 2 is Ni, Co, or Fe, and
[0049] p is 0≤p≤0.9.
[0050] For example, the secondary battery is a pouch-type battery. Or, the secondary battery is a cylindrical or prismatic battery. Effects of the invention
[0052] The cathode according to the present invention can achieve high rapid charge / discharge efficiency while maintaining an excellent capacity retention rate by controlling the viscosity, solid content, and orientation (OI) of the cathode slurry. Brief explanation of the drawing
[0054] Figure 1 is a graph showing the results of comparing the orientation degree (OI) of the first and second cathode active material layers according to the examples. Figure 2 is a graph showing the results of measuring the rapid charging time of secondary batteries for each example to comparative example. Figure 3 is a graph showing the results of measuring the discharge capacity retention rate (%) and resistance change rate (%) during high-temperature storage for secondary batteries with negative electrodes according to the examples and comparative examples. Specific details for implementing the invention
[0055] The present invention is capable of various modifications and may have various embodiments, and specific embodiments are to be described in detail in the detailed description.
[0056] However, this is not intended to limit the invention to specific embodiments, and it should be understood that it includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.
[0057] In the present invention, terms such as "comprising" or "having" are intended to specify the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not excluding in advance the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.
[0058] In addition, in this specification, "active material is oriented" means that a specific crystal plane representing the two-dimensional planar structure of the active material particles (e.g., the ab-axis crystal plane of graphite) is arranged to have a predetermined inclination with respect to the surface of the current collector, which may differ from the active material particles themselves being arranged to have a specific direction within the active material layer.
[0059] In addition, "low degree of orientation of the active material" means that the "degree of orientation (OI)" mentioned in this specification has a high value, which may mean that a specific crystal plane representing the two-dimensional planar structure of the active material contained in the active material layer (e.g., the ab-axis crystal plane of graphite) is arranged at a low angle (e.g., less than 45°) with respect to the surface of the current collector or is non-oriented. Conversely, "high degree of orientation of the active material" means that the "degree of orientation (OI)" has a low value, which may mean that the crystal plane of the active material contained in the active material layer is arranged at a high angle (e.g., an angle close to vertical, 45° or more; specifically 60° or more) with respect to the surface of the negative current collector.
[0060] Furthermore, in this specification, "crystal plane of an active material" refers to a plane forming the external shape of an active material crystal, and in the present invention, it may mean a crystal plane including a plane of the active material, or a crystal plane including the a-axis / b-axis / ab-axis of the active material crystal.
[0062] The present invention will be described in more detail below.
[0064] The present invention provides a method for manufacturing a negative electrode for a secondary battery. In one embodiment, the method for manufacturing a negative electrode for a secondary battery comprises the steps of: applying a negative electrode slurry onto a current collector; applying a magnetic field to the applied negative electrode slurry; drying; and rolling.
[0065] In the step of applying the above cathode slurry onto a current collector, the cathode slurry is controlled to have a viscosity of 5,500 cp to 12,000 cp and a solid content of 51 wt% to 55 wt%.
[0066] The above viscosity is an important factor affecting process efficiency or product quality during cathode manufacturing. The viscosity of the cathode slurry is in the range of 5,500cp to 12,000cp, 5,800cp to 12,000cp, 5,500cp to 11,500cp, 5,500cp to 7,500cp, 7,500cp to 10,000cp, 5,500cp to 10,000cp, or 6,000cp to 9,000cp.
[0067] If the viscosity of the cathode slurry is low, the cathode slurry applied to the current collector may flow sideways, resulting in an excessive sliding region. Additionally, due to the low viscosity, a problem arises where drying efficiency is significantly reduced. In particular, if the viscosity of the cathode slurry is excessively low, the degree of orientation of the active material may be significantly reduced during the drying process. Conversely, if the viscosity of the cathode slurry is high, the coating uniformity of the cathode slurry applied to the current collector may be reduced. Furthermore, due to the high viscosity, the orientation efficiency of the cathode active material under the application of a magnetic field may be significantly reduced.
[0068] The solid content of the above cathode slurry is in the range of 51 wt% to 55 wt%, 51 wt% to 54 wt%, 51.5 wt% to 53.5 wt%, 51 wt% to 53 wt%, 53 wt% to 54 wt%, or 51 wt% to 53 wt%. The solid content of the cathode slurry is a factor that directly affects the viscosity of the cathode slurry. In addition, the solid content of the above cathode slurry needs to be controlled by taking into account the drying time of the cathode slurry, etc.
[0070] The cathode active material layer formed through the above rolling step has an orientation index (OI) according to Formula 1 below in the range of 1 to 10.
[0071] [Equation 1]
[0072] OI = I 004 / I 110
[0073] In the above Equation 1,
[0074] I 004 represents the area of the peak indicating the (0,0,4) crystal plane of the carbon-based active material during X-ray diffraction (XRD) spectroscopic analysis of the cathode active material layer, and
[0075] I 110represents the area of the peak indicating the (1,1,0) crystal plane of the carbon-based active material during X-ray diffraction (XRD) spectroscopic analysis of the cathode active material layer.
[0076] In addition, under Condition 1 above, the orientation degree (OI) refers to the orientation degree of the cathode active material. The orientation degree (OI) of the cathode active material can serve as an indicator of the degree to which the ab-axis crystal planes of the carbon-based active material are oriented in a certain direction, specifically with respect to the surface of the cathode current collector, when measured by X-ray diffraction (XRD). In a specific example, the orientation degree (OI) shows peaks for graphite, which is a carbon-based active material, such as 2θ = 26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2° when measured by X-ray diffraction of the cathode active material layer. This represents the (0,0,2) plane, (1,0,0) plane, (1,0,1)R plane, (1,0,1)H plane, (0,0,4) plane, and (1,1,0) plane of graphite. Here, the peak appearing at 2θ=43.4±0.2° can be seen as an overlap between the peak corresponding to the (1,0,1)R plane of the cathode active material and the (1,1,1) plane of the current collector, e.g., copper (Cu).
[0077] The orientation degree (OI) of the cathode active material can be measured through the ratio of the areas obtained by integrating the respective intensities of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane and the peak at 2θ=77.5±0.2° representing the (1,1,0) plane.
[0078] Since the peak at 2θ = 54.7 ± 0.2° represents a crystal plane of the negative electrode active material that has a slope relative to the negative electrode current collector, the degree of orientation (OI) may indicate that the slope relative to the surface of the negative electrode current collector is close to 90° as its value approaches 0, and the slope relative to the surface of the negative electrode current collector is close to 0° or 180° as its value increases. That is, the negative electrode active material layer according to the present invention may be aligned such that the negative electrode active material has an angle of 60° or more, 70° or more, 70~90°, 80~90°, 65~85°, or 70~85° relative to the current collector. Accordingly, the degree of orientation (OI) of the negative electrode active material in the negative electrode active material layer may be lower compared to the case where the negative electrode active material is aligned at a low angle of less than 60°.
[0079] Here, the orientation degree (OI) represents the degree of orientation of the ab-axis crystal plane of the carbon-based active material, and does not represent the degree to which the carbon-based active material particles are oriented by rotating on their own within the negative electrode active material layer.
[0080] The present invention can secure an ion emission channel within the negative electrode active material layer that allows lithium ions to move more quickly by controlling the orientation (OI) of the carbon-based active material contained in the negative electrode active material layer as described above. As a result, the negative electrode of the present invention can prevent an increase in resistance caused by the long travel distance of lithium ions, thereby preventing high-rate charging performance from degrading due to electrical resistance and simultaneously improving high-rate discharge efficiency.
[0081] It was confirmed that the cathode satisfying condition 1 above has excellent rapid charging performance and capacity retention rate. By controlling the orientation degree (OI), rapid charging performance can be increased, and by simultaneously controlling the range (Span) value and the orientation degree (OI), the capacity retention rate can be increased.
[0082] Specifically, the orientation degree (OI) according to the above Equation 1 is in the range of 1 to 10, 1 to 6, 1 to 5, 2 to 10, 2 to 6, 2 to 4, or 2.5 to 3.7. In the present invention, it is important that the orientation degree (OI) of the negative electrode active material satisfies an appropriate range. Typically, regarding rapid charging and discharging, it is advantageous to control the orientation degree (OI) of the negative electrode active material to have a small value. However, it has been confirmed that if the orientation degree (OI) of the negative electrode active material is excessively small, the rapid charging and discharging performance is actually degraded.
[0083] In one embodiment, the cathode slurry comprises a carbon-based active material as the cathode active material. The carbon-based active material refers to a material having carbon atoms as its main component, and may include graphite. The graphite may include one or more of natural graphite and artificial graphite. For example, the carbon-based active material may include natural graphite or artificial graphite alone, or in some cases, may include a mixture of natural graphite and artificial graphite.
[0084] Specifically, the cathode slurry comprises natural graphite (GN) and artificial graphite (GA) as cathode active materials in a weight ratio of 60:40 to 40:60 (GA:GN). By including natural graphite and artificial graphite in the above mixing ratio, the carbon-based active material can solidify the adhesion between the cathode current collector and the cathode active material layer while achieving high orientation of the carbon-based active material on the surface of the cathode current collector. Specifically, the mixing ratio (GA:GN) of the natural graphite (GN) and artificial graphite (GA) is in the range of a weight ratio of 60:40 to 40:60, 55:45 to 35:65, 60:40 to 45:55, 48:52 to 58:42, 48:52 to 52:48, or 52:48 to 58:42. In the present invention, it was confirmed that controlling the content of natural graphite (GN) contained in the cathode slurry to be equal to or slightly higher than that of artificial graphite (GA) is advantageous for maintaining rapid charging performance and orientation.
[0085] The above carbon-based active material may have a spherical particle shape. In this case, the sphericity of the graphite particles may be 0.75 or higher, for example, 0.75 to 1.0; 0.75 to 0.95; 0.8 to 0.95; or 0.90 to 0.99. Here, "sphericity" may refer to the ratio of the shortest diameter (minor diameter) to the longest diameter (major diameter) among any diameters passing through the center of the particle. A sphericity of 1 indicates that the shape of the particle is spherical. The above sphericity can be determined by measuring using a particle shape analyzer or by analyzing the measured results after measuring the shape of the particle using a scanning electron microscope (SEM) or an energy dispersive spectrometer.
[0086] The present invention enables high electrical conductivity of the negative electrode active material layer by implementing the shape of the negative electrode active material to be close to spherical. Accordingly, a negative electrode comprising a spherical carbon-based active material can improve the capacity of a secondary battery and has the advantage of improving adhesion between the negative electrode active material layer and the current collector by increasing the specific surface area per unit weight of the negative electrode active material.
[0087] In another embodiment, the negative electrode active material layer may further include a silicon-based negative electrode active material. The silicon-based negative electrode active material is a general term for a material containing silicon (Si) as a main component. The present invention can increase the charge / discharge capacity of the negative electrode by containing a silicon-based negative electrode active material.
[0088] The above silicon-based negative electrode active material comprises silicon (Si), silicon carbide (SiC), a composite of carbon and silicon (Si / C), and silicon oxide (SiO₂). q ..., provided that it includes one or more of 0.8≤q≤2.5). Specifically, such silicon-based negative electrode active materials may include silicon (Si), silicon carbide (SiC), silicon monoxide (SiO), or silicon dioxide (SiO2), and these may be included alone or used in combination in the second negative electrode active material layer. When silicon monoxide (SiO) and silicon dioxide (SiO2) are uniformly mixed or composited and included in the negative electrode active material layer as the silicon-based negative electrode active materials, they are silicon oxide (SiO2 q , provided that 0.8≤q≤2.5) can be expressed. In addition, the silicon-based negative electrode active material may be doped with or alloyed with Li, Mg, Al, Ca, or Ti. If the silicon-based negative electrode active material contains oxygen (O), volume expansion during charging can be suppressed. Furthermore, a carbon-silicon composite (Si-C) may be manufactured by surface treating the surface with a carbon coating layer or the like to improve the electrical conductivity of the negative electrode active material, or by mixing silicon and carbon powders.
[0089] In addition, the content of the silicon-based negative electrode active material may be in the range of 0.1 to 30 weight% based on the total weight of the negative electrode active material contained in the negative electrode slurry. Specifically, the content of the silicon-based negative electrode active material may be in the range of 0.5 to 20 weight%, 1 to 9 weight%, 5 to 15 weight%, 3 to 7 weight%, 11 to 19 weight%, 13 to 17 weight%, 15 to 20 weight%, 10 to 30 weight%, 20 to 30 weight%, 15 to 25 weight%, or 9 to 22 weight%. By adjusting the content ratio of the carbon-based active material and the silicon-based negative electrode active material to the above ranges, the present invention can improve the charge capacity per unit mass while reducing lithium consumption and irreversible capacity loss during the initial charge and discharge of the secondary battery. In addition, by minimizing the volume change of the negative electrode active material layer during charging and discharging of the secondary battery, the structural stability of the negative electrode active material layer can be improved, thereby extending the lifespan of the secondary battery.
[0090] In addition, the silicon-based negative electrode active material has an average particle size (D) of 0.1㎛ to 10㎛. 50 It can represent , Ds), specifically 0.1㎛ to 5㎛; 0.1㎛ to 3㎛; 0.1㎛ to 1㎛; 0.5㎛ to 2㎛; 0.5㎛ to 5㎛; 1㎛ to 5㎛; 3㎛ to 7㎛; 5㎛ to 10㎛; 1㎛ to 3㎛; 4㎛ to 9㎛; 0.1㎛ to 0.9㎛; 0.8㎛ to 1.2㎛; or an average particle size (D) of 0.3㎛ to 0.8㎛. 50 It can represent ).
[0091] When the minimum particle size of the silicon-based negative electrode active material is less than 0.1 μm, it is difficult to uniformly disperse the negative electrode active material layer. As the charging and discharging of the secondary battery proceeds, the redox reaction between the aggregated and non-aggregated regions of the silicon-based negative electrode active material is induced unevenly, which can accelerate the degradation of the negative electrode active material layer. In addition, if the maximum particle size of the silicon-based negative electrode active material exceeds 10 μm, it is difficult to control the crystal plane of the silicon-based negative electrode active material, and the expansion rate per unit area of the negative electrode active material layer increases significantly during the charging and discharging of the secondary battery. Consequently, there is a problem in that the cycle characteristics decrease significantly as the charging and discharging are repeated.
[0092] In one embodiment, the orientation index (OI) of the cathode slurry that has undergone the step of applying the magnetic field is in the range of 0.1 to 5. Specifically, the orientation index (OI) of the cathode slurry is in the range of 0.1 to 5, 0.1 to 4.5, 0.1 to 3.5, 0.1 to 3, 0.5 to 3, 0.5 to 2, or 0.5 to 1.5. The orientation index (OI) of the cathode slurry takes into account that the value changes during the subsequent drying or rolling step. By controlling the orientation index (OI) of the cathode slurry to the above range, process efficiency can be increased and the desired orientation index (OI) of the cathode active material layer can be achieved.
[0093] The step of applying the magnetic field is a process of orienting active material particles by applying a magnetic field to a non-drying cathode active material. In one example, in the step of applying the magnetic field, the strength of the applied magnetic field is in the range of 2,000G to 12,000G. Specifically, the strength of the applied magnetic field is in the range of 2,500G to 12,000G, 2,000G to 9,000G, 2,500G to 9,500G, 3,500G to 12,000G, 3,500G to 10,000G, 3,500G to 9,500G, 5,500G to 9,000G, or 5,500G to 7,000G. When the strength of the applied magnetic field increases, the degree of orientation of the negative electrode active material increases, and the orientation degree (OI) decreases. However, the present invention improves process efficiency and the performance of a secondary battery by controlling the strength of the applied magnetic field to an appropriate range. If the strength of the applied magnetic field increases above a certain level, energy consumption increases and the magnetic field application efficiency decreases rapidly. In addition, if the orientation degree (OI) is too small, the interfacial adhesion may decrease as the contact area between the active material oriented in the vertical direction and the current collector decreases. The time for applying the magnetic field can be controlled within a range of 1 second to 30 seconds, a range of 2 seconds to 20 seconds, or a range of 3 seconds to 10 seconds.
[0094] The above magnetic field application step may be a step for controlling the crystal characteristics of the cathode active material contained in the cathode slurry. Specifically, this step aligns the ab-axis crystal plane of the carbon-based active material to have a high angle with respect to the cathode current collector by applying a magnetic field to the surface of the cathode slurry coated on the cathode current collector. In particular, the (1,1,1) crystal plane characteristics of the silicon-based cathode active material contained in the second cathode slurry can be controlled.
[0095] At this time, the magnetic field may be applied by magnetic parts positioned at the top and bottom of a cathode current collector that is moved with a cathode slurry coated on its surface. In addition, the polarities of the magnetic parts positioned at the top and bottom may be different from each other.
[0096] In addition, the orientation (OI) of the carbon-based active material contained in the cathode slurry can be controlled by the strength of the applied magnetic field, and accordingly, the step of applying the magnetic field can be performed under a predetermined magnetic field strength condition.
[0097] In addition, the present invention may include a step of drying and rolling the cathode after the step of applying the magnetic field.
[0098] At this time, the step of drying the cathode can be applied without particular limitation as long as it is a method that can maintain the orientation of the carbon-based active material contained within the cathode active material layer.
[0099] For example, the drying step may be performed by applying thermal energy to the cathode slurry using a hot air dryer, a vacuum oven, etc. The drying step may be performed in a temperature range of 80°C to 350°C, 100°C to 250°C, or 100°C to 200°C. The drying method or drying temperature in the drying step may be selected within a range that induces complete evaporation of the solvent while preventing damage to the binder component.
[0100] In addition, the step of rolling the dried cathode is a step of increasing the density of the cathode active material layer by applying pressure to the dried cathode slurry using a roll press or the like. At this time, the rolling can be performed under temperature conditions higher than room temperature.
[0101] Specifically, the rolling may be performed at a temperature of 25°C to 100°C, more specifically at a temperature of 60°C to 100°C; 75°C to 100°C; 85°C to 100°C; 50°C to 90°C; 60°C to 80°C; or 65°C to 90°C. Specifically, the rolling may be performed at a rolling speed of 2 m / s to 7 m / s, and more specifically at a speed of 2 m / s to 6.5 m / s; 2 m / s to 6 m / s; 2 m / s to 5.5 m / s; 2 m / s to 5 m / s; 2 m / s to 4.5 m / s; 2 m / s to 4 m / s; 2.5 m / s to 4 m / s; 2.5 m / s to 3.5 m / s; 3.5 m / s to 5 m / s. The rolling can be performed at a rolling speed of 5 m / s to 7 m / s; 5.5 m / s to 6.5 m / s; or 6 m / s to 7 m / s. In addition, the rolling can be performed under pressure conditions of 50 MPa to 200 MPa, specifically under pressure conditions of 50 MPa to 150 MPa; 50 MPa to 100 MPa; 100 MPa to 200 MPa; 150 MPa to 200 MPa; or 80 MPa to 140 MPa.
[0102] The porosity (%) of the cathode active material layer that has undergone the above rolling step is in the range of 25% to 35%. Specifically, the porosity (%) of the cathode active material layer is in the range of 25% to 35%, 28% to 35%, 25% to 32%, 28% to 32%, or 28.5% to 31%. The porosity of the cathode active material layer is controlled by considering the cathode capacity and electrolyte impregnation properties.
[0103] In one embodiment, the method for manufacturing a negative electrode for a secondary battery according to the present invention includes forming a negative electrode active material layer on both sides of a current collector. Specifically, the method for manufacturing a negative electrode for a secondary battery repeats the steps of applying a negative electrode slurry onto a current collector, applying a magnetic field, and drying in two process cycles. Specifically, in the first process cycle of the two process cycles, a negative electrode slurry is applied to the top surface, which is one side of the current collector, to form a first negative electrode active material layer. In addition, in the second process cycle, a negative electrode slurry is applied to the back surface, which is the opposite side of the current collector, to form a second negative electrode active material layer.
[0104] In one example, in the first process cycle, the magnetic field strength applied during the magnetic field application step is in the range of 2,000G to 9,000G. Additionally, in the second process cycle, the magnetic field strength applied during the magnetic field application step is in the range of 2,500G to 9,500G. Specifically, the magnetic field strengths applied in the first and second process cycles, respectively, are the same, or the difference in magnetic field strength is 500G or less. For example, the difference in magnetic field strength applied in the first and second process cycles, respectively, is 500G or less, 300G or less, or in the range of 50G to 500G. For example, the magnetic field strength applied in the second process cycle can be controlled to be relatively high.
[0105] In another embodiment, the difference in the average orientation index (OI) of the first and second cathode active material layers is 1.5 or less. The difference in the average orientation index (OI) of the first and second cathode active material layers is 1.5 or less, 1 or less, 0.8 or less, in the range of 0.01 to 1.5, in the range of 0.1 to 1, in the range of 0.1 to 0.8, or in the range of 0.1 to 0.5. In terms of cathode uniformity, it is advantageous to control the difference in the average orientation index (OI) of the first and second cathode active material layers to be small. However, a difference in the average orientation index (OI) of the first and second cathode active material layers may occur due to process differences between the top surface coating and the back surface coating of the current collector. One method to reduce this difference in orientation index (OI) is to vary the strength of the magnetic field applied in the first and second process cycles. For example, this difference can be reduced by making the strength of the magnetic field applied in the second process cycle higher. Another method to reduce this difference in orientation (OI) is to appropriately control process conditions. Specifically, the difference in orientation (OI) between the first and second cathode active material layers can be reduced by controlling the viscosity, solid content, and magnetic field strength of the cathode slurry. For example, it was experimentally confirmed that by introducing process conditions that control the orientation (OI) of the cathode active material layer to a level of 2.5 to 3.5, the difference in orientation (OI) between the first and second cathode active material layers can be reduced to 0.8 or less, or 0.5 or less.
[0107] The present invention provides a negative electrode for a secondary battery manufactured by applying the manufacturing method described above. In one embodiment, the negative electrode for a secondary battery according to the present invention comprises a current collector; and a negative electrode active material layer formed on one or both sides of the current collector. Additionally, the negative electrode active material layer has an orientation index (OI) according to Formula 1 below in the range of 1 to 10.
[0108] [Equation 1]
[0109] OI = I 004 / I 110
[0110] In the above Equation 1,
[0111] I 004 represents the area of the peak indicating the (0,0,4) crystal plane of the carbon-based active material during X-ray diffraction (XRD) spectroscopic analysis of the cathode active material layer, and
[0112] I 110 represents the area of the peak indicating the (1,1,0) crystal plane of the carbon-based active material during X-ray diffraction (XRD) spectroscopic analysis of the cathode active material layer.
[0113] A detailed explanation of Equation 1 is redundant with what was mentioned earlier.
[0114] The above-mentioned negative electrode active material layer is a layer that implements the electrical activity of the negative electrode and includes, as a main component, a negative electrode active material that implements an electrochemical redox reaction during the charging and discharging of the battery.
[0115] At this time, the negative active material layer may have a structure in which the negative active material layer is laminated on one or both sides of a negative current collector. The negative active material layer of such a structure can improve the performance of the negative electrode by controlling the type or content of the components contained therein according to specific purposes, such as increasing the energy efficiency of the battery or improving the adhesion between the active material layer and the current collector. For example, the negative active material layer may optionally include a silicon-based negative active material having a high charge / discharge capacity of the battery.
[0116] In one embodiment, the negative electrode active material comprises a carbon-based active material. The carbon-based active material comprises one or more of natural graphite and artificial graphite. Additionally, the negative electrode active material may further comprise a silicon-based negative electrode active material.
[0117] For example, the above-mentioned cathode active material layer comprises natural graphite (GN) and artificial graphite (GA) as cathode active materials in a weight ratio of 60:40 to 30:60 (GA:GN).
[0118] In one example, a negative electrode for a secondary battery according to the present invention comprises a current collector; a first negative active material layer formed on one side of the current collector; and a second negative active material layer formed on the opposite side of the current collector. In addition, the difference in the average orientation index (OI) between the first and second negative active material layers is 1.5 or less.
[0119] In addition, the carbon-based active material and silicon-based negative electrode active material contained in the negative electrode active material layer may be included in a range of 85 parts by weight to 98.5 parts by weight based on the total weight of the negative electrode active material layer, and specifically, may be included in an amount of 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more.
[0120] Meanwhile, the average thickness of the negative electrode active material layer may be 100 μm to 800 μm, and specifically, may be in the range of 100 μm to 300 μm; 200 μm to 800 μm; or 300 μm to 800 μm. By adjusting the average thickness of the negative electrode active material layer to the above range, the crystal characteristics of the negative electrode active material can be easily controlled, and thereby, the high-rate charge / discharge characteristics of a secondary battery including the negative electrode of the present invention can be improved.
[0121] In addition, the negative electrode active material layer according to the present invention may optionally further include a conductive material, a binder, other additives, etc., along with the negative electrode active material which is the main component, as needed.
[0122] The above conductive material may include one or more types such as carbon black, acetylene black, ketjen black, carbon nanotubes, carbon fibers, etc., but is not limited thereto.
[0123] As an example, the above-mentioned cathode active material layer may contain carbon black, carbon nanotubes, carbon fibers, etc., as a conductive material, either alone or in combination.
[0124] At this time, the content of the conductive material may be 0.1 to 10 parts by weight per 100 parts by weight of the entire negative electrode active material layer, and specifically, may be 0.1 to 8 parts by weight, 0.1 to 7 parts by weight, 0.1 to 3 parts by weight, 2 to 6 parts by weight, or 0.5 to 2 parts by weight. By controlling the content of the conductive material within the above range, the present invention can prevent the decrease in charging capacity caused by an increase in the resistance of the negative electrode due to a low content of the conductive material, and can prevent problems such as a decrease in charging capacity caused by a decrease in the content of the negative electrode active material due to an excessive amount of conductive material, or a decrease in rapid charging characteristics due to an increase in the loading amount of the negative electrode active material layer.
[0125] In addition, the binder may be appropriately applied as a component that assists in the bonding of the negative electrode active material and the conductive material and the bonding to the current collector, within a range that does not degrade the electrical properties of the electrode, but specifically, it may include one or more selected from the group consisting of vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidenefluoride (PVdF), polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene butadiene rubber (SBR), and fluororubber.
[0126] The content of the binder may be 0.1 to 10 parts by weight per 100 parts by weight of the entire negative electrode active material layer, and specifically, may be 0.1 to 8 parts by weight, 0.1 to 7 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight. By controlling the content of the binder contained in the negative electrode active material layer to the above range, the present invention can prevent the adhesion of the active material layer from being reduced due to a low content of binder or the electrical properties of the electrode from being reduced due to an excessive amount of binder.
[0127] In addition, the above-mentioned negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, nickel, titanium, calcined carbon, etc. may be used, and in the case of copper or stainless steel, surface-treated carbon, nickel, titanium, silver, etc. may be used. Furthermore, the average thickness of the above-mentioned negative electrode current collector can be appropriately applied in the range of 1 to 150 μm, taking into consideration the conductivity and total thickness of the negative electrode being manufactured.
[0129] In addition, the present invention provides a secondary battery comprising the negative electrode described above. In one embodiment, the secondary battery according to the present invention comprises an electrode assembly having a structure in which a negative electrode, a positive electrode, and a separator are located between the negative electrode and the positive electrode. The negative electrode is as described above.
[0130] A lithium secondary battery according to the present invention comprises an electrode assembly having a structure in which a plurality of positive electrodes and a plurality of negative electrodes are alternately arranged and a separator is positioned between them. The lithium secondary battery is equipped with the negative electrode of the present invention described above, and since it has not only a high charge / discharge capacity but also excellent high-rate charge / discharge characteristics, it can be usefully used as a power source for medium-to-large devices such as electric vehicles.
[0131] At this time, since the above-mentioned cathode has the same configuration as the above-described configuration, a detailed explanation is omitted.
[0132] In addition, the anode comprises an anode active material layer containing an anode active material on an anode current collector, and the anode active material layer may optionally further include a conductive material, a binder, other additives, etc., as needed.
[0133] The above-mentioned positive electrode active material is a material capable of causing an electrochemical reaction on a positive electrode current collector and may include one or more of lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2, which are capable of reversibly intercalating and deintercalating lithium ions:
[0134] [Chemical Formula 1]
[0135] Li x [Ni y Co z Mn w M 1 v ]O2
[0136] [Chemical Formula 2]
[0137] LiMn p M 2 1-p O4
[0138] In the above Chemical Formulas 1 and 2,
[0139] M 1 It is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0140] x, y, z, w, and v are 1.0≤x≤1.30, 0.5≤y<1, 0, respectively. <z≤0.3, 0<w≤0.3, 0≤v≤0.1이되, y+z+w+v=1이고,
[0141] M 2 is Ni, Co, or Fe, and
[0142] p is 0≤p≤0.9.
[0143] The lithium metal oxides represented by the above chemical formulas 1 and 2 are materials containing high amounts of nickel (Ni) and manganese (Mn), respectively, and when used as cathode active materials, they have the advantage of being able to stably supply high capacity and / or high voltage electricity compared to conventionally used cathode active materials such as iron phosphate oxide (LiFeO4).
[0144] In this case, LiNi is used as the lithium metal oxide represented by the above chemical formula 1. 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2, LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 The lithium metal oxide represented by the above chemical formula 2 may include O2, etc., and is LiNi 0.7 Mn 1.3 O4; LiNi 0.5 Mn 1.5 O4; LiNi 0.3 Mn 1.7 It may include O4, etc., and can be used alone or in combination.
[0145] In addition, the above-mentioned positive active material may be included in an amount of 85 parts by weight or more based on the weight of the positive active material layer, and specifically, in an amount of 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more.
[0146] In addition, the above-mentioned positive active material layer may further include a conductive material, a binder, other additives, etc., along with the positive active material.
[0147] At this time, the conductive material is used to improve the electrical performance of the anode, and while commonly used in the industry may be applied, specifically, it may include one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Denka black, Ketjen black, Super-P, Channel black, furnace black, lamp black, thermal black, graphene, and carbon nanotubes.
[0148] In addition, the conductive material may be included in an amount of 0.1 to 5 parts by weight based on the weight of each positive active material layer, and specifically, may be included in an amount of 0.1 to 4 parts by weight; 2 to 4 parts by weight; 1.5 to 5 parts by weight; 1 to 3 parts by weight; 0.1 to 2 parts by weight; or 0.1 to 1 part by weight.
[0149] In addition, the binder serves to bind the cathode active material, cathode additive, and conductive material together, and any binder having this function can be used without particular limitation. Specifically, the binder may include one or more resins selected from the group consisting of polyvinylidenefluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinylidenefluoride (PVdF), polyacrylonitrile, polymethylmethacrylate, and copolymers thereof. As one example, the binder may include polyvinylidenefluoride.
[0150] In addition, the binder may be included in an amount of 1 to 10 parts by weight based on the weight of each positive electrode active material layer, specifically 2 to 8 parts by weight; or 1 to 5 parts by weight.
[0151] The total thickness of the above positive active material layer is not particularly limited, but specifically it may be 50㎛ to 300㎛, and more specifically it may be 100㎛ to 200㎛; 80㎛ to 150㎛; 120㎛ to 170㎛; 150㎛ to 300㎛; 200㎛ to 300㎛; or 150㎛ to 190㎛.
[0152] In addition, the above-mentioned positive electrode may be used as a positive electrode current collector that has high conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. may be used, and in the case of aluminum or stainless steel, surface-treated materials such as carbon, nickel, titanium, silver, etc. may be used. Furthermore, the average thickness of the above-mentioned current collector may be appropriately applied in the range of 3 to 150 μm, taking into consideration the conductivity and total thickness of the manufactured positive electrode.
[0153] In addition, the separator interposed between the anode and the cathode of each unit cell is an insulating thin film having high ion permeability and mechanical strength, and is not particularly limited as long as it is commonly used in the industry, but specifically, it may be used as one comprising one or more polymers selected from chemically resistant and hydrophobic polypropylene; polyethylene; and polyethylene-propylene copolymer. The separator may have the form of a porous polymer substrate such as a sheet or nonwoven fabric containing the aforementioned polymer, and in some cases, it may have the form of a composite separator in which organic or inorganic particles are coated on the porous polymer substrate by an organic binder. Furthermore, the separator may have an average pore diameter of 0.01 to 10 μm and an average thickness of 5 to 300 μm.
[0154] The above secondary battery may be a prismatic, cylindrical, or pouch-type battery. Depending on the shape of the secondary battery, a wound-type or stacked-type electrode assembly is applied. The secondary battery according to the present invention can be applied more effectively to a wound-type electrode assembly. A wound-type electrode assembly is a form in which a positive electrode, a separator, and a negative electrode are stacked and then a core is wound around the center. In the present invention, the wound-type electrode assembly includes an electrode assembly having a cylindrical structure and / or a jelly-roll structure. During the process of repeated charging and discharging, the wound-type electrode assembly exhibits a difference in the degree of degradation between the negative electrode in the central region near the core and the negative electrode in the outer region. This difference in the degree of degradation by region degrades cell performance and, in particular, acts as a cause for a decrease in capacity retention rate. The present invention can reduce this difference in the degree of degradation by region by applying the previously described negative electrode to the wound-type electrode assembly. The secondary battery to which the above-described wound-type electrode assembly is applied is a cylindrical or prismatic secondary battery, for example, a cylindrical secondary battery.
[0156] The present invention will be explained in more detail below through examples and experimental examples. However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.
[0158] Comparative Examples 1–5 and Examples 1–12. Preparation of negative electrodes for secondary batteries
[0159] A carbon-based active material, carbon black as a conductive material, and styrene butadiene rubber (SBR) as a binder were prepared. Then, 96 parts by weight of graphite, 1.5 parts by weight of carbon black, and 2.5 parts by weight of styrene butadiene rubber (SBR) were mixed with water to prepare a cathode slurry. The detailed composition of the cathode slurry is as shown in Table 1 below.
[0160] The manufactured cathode slurry was discharged onto a copper foil (thickness: 10㎛) being transported roll-to-roll (transport speed: 5 m / min).
[0161] A permanent magnet having a length ratio of 110–120% based on the width direction length of the cathode slurry was placed on top of the coated cathode slurry, and a magnetic field was applied for 10 seconds by adjusting the magnetic field strength as shown in Tables 1 and 2 below. The cathode slurry to which the magnetic field was applied was hot-air dried to form a cathode active material layer. The formed cathode active material layer was rolled at 50±1℃ under a pressure of 100–150 MPa and a feed speed of 3 m / s to manufacture a cathode for a lithium secondary battery (average thickness of the cathode active material layer: 230 μm).
[0162] No. Active material composition Porosity (%) Viscosity (cp) Solid content (wt%) Magnetic field strength (G) Comparative Example 1 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 5,000 50.25 Unauthorized Comparative Example 2 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 6,000 51.52 Unauthorized Comparative Example 3 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 9,000 53.45 Unauthorized Comparative Example 4 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 11,000 53.91 Unauthorized Comparative Example 5 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 13,000 55.02 3,000
[0164] No. Active material composition Porosity (%) Viscosity (cp) Solid content (wt%) Magnetic field strength (G) Example 1 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 6,000 51.52 3,000 Example 2 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 6,000 51.52 4,000 Example 3 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 6,000 51.52 6,000 Example 4 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 6,000 51.52 8,050 Example 5 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 9,000 52.00 3,000 Example 6 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 9,000 52.00 4,000 Example 7 A mixture of 55 parts by weight of natural graphite and 45 parts by weight of artificial graphite 29.5 9,000 52.00 4,000 Example 8 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 9,000 52.00 6,000 Example 9 A mixture of 55 parts by weight of natural graphite and 45 parts by weight of artificial graphite 29.5 9,000 52.00 6,000 Example 10 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 9,000 52.00 8,050 Example 11 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 11,000 53.45 3,000 Example 12 A mixture of 50 parts by weight of natural graphite and 50 parts by weight of artificial graphite 29.5 11,000 53.45 8,050
[0166] Experimental Example 1. Measurement of Orientation Degree (OI)
[0167] The spectrum was measured by performing X-ray diffraction (XRD) spectroscopy on the cathode samples. In this case, the X-ray diffraction (XRD) spectroscopic analysis was performed by targeting each cathode active material contained in the cathode active material layer, and the measurement conditions for X-ray diffraction (XRD) are as follows:
[0168] - Target: Cu(Kα-line) graphite monochromator
[0169] - Slit: Diverging slit = 1 degree, Receiving slit = 0.1 mm, Scattering slit = 1 degree
[0170] - Measurement zone: (1,1,0) plane: 76.5 degrees < 2θ < 78.5 degrees / (0,0,4) plane: 53.5 degrees < 2θ < 56.0 degrees.
[0172] Then, the area integral values of the peaks representing the (0,0,4) crystal plane and the (1,1,0) crystal plane are calculated from the spectrum measured with the carbon-based active material as the target, and the ratio of these areas (I 004 / I 110 The orientation degree (OI) for each region was calculated by calculating ).
[0173] Using the calculated orientation degree (OI), the value according to Equation 1 mentioned earlier was also calculated, and the results are shown in Tables 3 and 4 below. Specifically, for Examples 1 to 12, the orientation degree (OI) was measured before and after the rolling process, respectively, and is shown in Table 3 below.
[0174] No. Orientation (OI) before rolling Orientation (OI) after rolling Example 1 1.73 7.58 Example 2 1.53 6.35 Example 3 1.21 4.52 Example 4 0.70 3.12 Example 5 1.37 4.51 Example 6 1.23 3.98 Example 7 1.22 3.57 Example 8 0.95 3.05 Example 9 0.93 2.85 Example 10 0.39 1.26 Example 11 3.34 9.24 Example 12 1.29 4.69
[0175] Referring to Table 3 above, it can be seen that the orientation degree (OI) value before rolling increases significantly during the rolling process. An increase in the orientation degree (OI) value means that the degree of orientation of the active material is reduced due to the pressure applied during the rolling process.
[0176] Examples 1 to 4 are samples in which the cathode slurry viscosity was controlled to 6,000 cp and different magnetic field strengths were applied. When examining the orientation degree (OI) measurement results for Examples 1 to 5, it was confirmed that when the viscosity and solid content are the same, the orientation degree (OI) decreases as the applied magnetic field strength increases.
[0177] Examples 11 and 12 are samples in which the cathode slurry viscosity was controlled to 11,000 cp and different magnetic field strengths were applied. Compared to Examples 1 to 4, it can be seen that as the viscosity of the cathode slurry increases, the orientation degree (OI) also increases.
[0178] However, Examples 5, 6, 8, and 10 are samples in which the cathode slurry viscosity was controlled to 9,000 cp and different magnetic field strengths were applied. Compared to Examples 1 to 4, Examples 5, 6, 8, and 10 show a tendency for relatively low orientation (OI) despite the increased viscosity of the cathode slurry. In particular, Example 10 shows the lowest orientation (OI). Through this, it was confirmed that a more appropriate orientation (OI) can be achieved by controlling the viscosity and solid content of the cathode slurry within a specific range.
[0179] In addition, Examples 7 and 9 are samples in which the content of natural graphite was controlled to 55 parts by weight during the preparation of the cathode slurry. Comparing Examples 6 and 7, the cathode was prepared under the same conditions, but Example 7 is a case where the content of natural graphite is relatively higher. It can be seen that Examples 6 and 7 show similar levels of orientation (OI) before rolling, but differ in the orientation (OI) after rolling. Furthermore, comparing Examples 8 and 9, the cathode was prepared under the same conditions, but Example 9 is a case where the content of natural graphite is relatively higher. It can be seen that Examples 8 and 9 show similar levels of orientation (OI) before rolling, but differ in the orientation (OI) after rolling. Through this, it was confirmed that increasing the content of natural graphite in the cathode slurry can suppress changes in orientation (OI) induced during the rolling process.
[0181] In addition, for Comparative Examples 1 to 5, the orientation degree (OI) of the negative electrode active material layer subjected to the rolling process was measured and is shown in Table 4 below. It can be seen that the orientation degree (OI) of the samples of Comparative Examples 1 to 5 exceeds 10 after rolling. Therefore, for the samples of Comparative Examples 1 to 5, the orientation degree (OI) before rolling was not measured separately.
[0182] No. Orientation (OI) Comparative Example 1 16.9 Comparative Example 2 16.8 Comparative Example 3 17.1 Comparative Example 4 17.3 Comparative Example 5 10.5
[0183] Referring to Table 4, Comparative Examples 1 to 4 are cases where no magnetic field is applied. It can be seen that Comparative Examples 1 to 4 have an orientation degree (OI) of approximately 17. In addition, Comparative Example 1 is a case where the viscosity and solid content are controlled to be relatively low, which results in an excessive increase in drying time and a significant decrease in productivity.
[0184] Comparative Example 5 is a case where a magnetic field of strength of 3,000 G was applied. However, Comparative Example 5 is a case where the viscosity of the cathode slurry is excessively high, and as a result, it can be seen that the orientation effect of the magnetic field application is very low.
[0186] Experimental Example 2. Measurement of Orientation Degree (OI) of Double-Sided Coated Cathode
[0187] A cathode was manufactured by the method according to Examples 5, 6, 8, and 10, wherein double-sided coating was performed based on a current collector (Examples 5-a, 6-a, 8-a, 10-a). Specifically, a cathode slurry was discharged onto one side (top side) of a copper foil and dried to form a first cathode material layer. A cathode slurry was discharged onto the opposite side (back side) of the copper foil and dried to form a second cathode active material layer. Then, a cathode for a secondary battery was manufactured through a rolling process.
[0188] For the above-mentioned cathode sample, the orientation degree (OI) was calculated for the first and second cathode active material layers formed on both sides (top side and back side) of the copper foil. The process for calculating the orientation degree (OI) is the same as described in Experimental Example 1. The results of the orientation degree (OI) calculation are shown in Table 5 and Figure 1 below.
[0189] No. Orientation degree (OI) of the first active material layer Orientation of the second active material layer (OI) Difference in orientation (△OI) Example 5-a 4.51 5.71 1.2 Example 6-a 3.98 4.78 0.8 Example 8-a 3.05 3.35 0.3 Example 10-a 1.26 2.66 1.4
[0190] Referring to Table 5 and Figure 1, it can be seen that the cathode according to Example 8-a has the smallest difference in orientation degree (OI) between the first and second active material layers. It was confirmed that by adjusting the orientation degree (OI) of the cathode active material layer to an appropriate range, the uniformity of the orientation degree (OI) between the top surface and the back surface can be improved. When comparing the results of Example 8-a and 10-a, it can be seen that although the cathode according to Example 10-a has a small orientation degree (OI) value, the difference in orientation degree between the first and second active material layers is actually larger.
[0192] Experimental Example 3. Evaluation of Rapid Charging Performance
[0193] Secondary battery manufacturing
[0194] LiNi with a particle size of 5㎛ as a cathode active material 0.7 Co 0.1 Mn 0.1 Al 0.1 O2 was prepared and mixed with N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 as a carbon-based conductive agent and binder to form a slurry, which was then coated onto a thin aluminum plate. The loading amount of the anode slurry was 4.43 mg / 25 cm². 2 It was controlled to the level. Then, 120 The anode was manufactured by drying in a vacuum oven and then rolling.
[0195] An electrode assembly was manufactured by winding the electrodes with a separator made of 18 μm polypropylene interposed between the anode obtained above and the previously manufactured cathode. After loading the manufactured electrode assembly into a cylindrical case, an electrolyte composition was injected to assemble a 1 Ah lithium secondary battery.
[0197] Rapid charging time measurement
[0198] The Quick Charge (QC) time (min) was measured using each manufactured secondary battery. Specifically, for each secondary battery, charging was performed under conditions of 35°C and 3°C. The time (min) required to charge from an SOC of 8% to an SOC of 80% was calculated. The results of the calculation are shown in Table 6 and Figure 2 below. In Table 6 below, the QC improvement rate (%) was calculated based on the Quick Charge time of the secondary battery using the negative electrode of Comparative Example 3.
[0199] No. QC(min) QC Improvement Rate (%) Comparative Example 3 29.4 - Example 3 26.5 9.9% Example 4 24.1 18.0% Example 5 26.4 10.2% Example 6 24.8 15.6% Example 7 24.2 17.7% Example 8 23.8 19.0% Example 9 24.5 16.7% Example 10 25.2 4.9%
[0200] Referring to Table 6 and Figure 2, it can be seen that the rapid charging time of the secondary batteries using the cathodes of Examples 3 to 10, respectively, is improved compared to the secondary battery using the cathode of Comparative Example 3. In particular, it was confirmed that the rapid charging time of the secondary batteries using the cathodes according to Examples 4 and 8, respectively, is significantly improved.
[0202] Experimental Example 4. Life Performance Evaluation
[0203] Life evaluation was performed on each secondary battery according to Experimental Example 5. Specifically, when each secondary battery sample containing a negative electrode according to Comparative Example 2 and Examples 5, 6, and 8 was stored at 60°C, the discharge capacity retention rate (%) and the resistance change rate (%) were measured. For each secondary battery sample, the discharge capacity retention rate (%) and the resistance change rate (%) were each measured three times, and the average value was calculated.
[0204] The above discharge capacity retention rate (%) was measured for each secondary battery sample under storage conditions of SOC 100 (%) and 60℃ according to the storage period.
[0205] In addition, for each secondary battery sample, the resistance change rate (%) was measured according to the storage period under SOC 50 (%) conditions, and the resistance measurement was performed for 10 seconds.
[0206] The evaluation results are illustrated in FIG. 3. FIG. 3 is a graph showing the results of measuring the discharge capacity retention rate (%) and the resistance change rate (%) during high-temperature storage for secondary batteries with negative electrodes according to each example to comparative example. Referring to FIG. 3, it can be seen that as the strength of the applied magnetic field increases, the discharge capacity retention rate (%) tends to decrease and the resistance change rate (%) tends to increase. However, the present invention minimizes the decrease in the discharge capacity retention rate (%) or the increase in the resistance change rate (%) by controlling the strength of the applied magnetic field to an appropriate range.
[0208] Although the present invention has been described above with reference to preferred embodiments, those skilled in the art or those with ordinary knowledge in the art will understand that various modifications and changes can be made to the present invention without departing from the spirit and technical scope of the invention as described in the claims set forth below.
[0209] Therefore, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification, but should be determined by the claims.
Claims
Claim 1 A method for manufacturing a negative electrode for a secondary battery, comprising the steps of: applying a negative electrode slurry having a viscosity in the range of 5,500 to 12,000 cp and a solid content in the range of 51 wt% to 55 wt% onto a current collector; applying a magnetic field to the applied negative electrode slurry; drying; and rolling, wherein the negative electrode active material layer formed through the rolling step has an orientation index (OI) in the range of 1 to 10 according to the following Equation 1: [Equation 1] OI = I 004 / I 110 In the above Equation 1, I 004 represents the area of the peak indicating the (0,0,4) crystal plane of the carbon-based active material during X-ray diffraction (XRD) spectroscopic analysis of the cathode active material layer, and I 110 represents the area of the peak indicating the (1,1,0) crystal plane of the carbon-based active material during X-ray diffraction (XRD) spectroscopic analysis of the cathode active material layer. Claim 2 A method for manufacturing a negative electrode for a secondary battery according to claim 1, wherein the negative electrode slurry comprises natural graphite (GN) and artificial graphite (GA) as negative electrode active materials in a weight ratio of 60:40 to 40:60 (GA:GN). Claim 3 A method for manufacturing a negative electrode for a secondary battery according to claim 1, wherein the negative electrode slurry further comprises a silicon-based negative electrode active material, and the content of the silicon-based negative electrode active material is in the range of 0.1 wt% to 30 wt% based on the total weight of the negative electrode active material contained in the negative electrode slurry. Claim 4 In claim 3, the silicon-based negative electrode active material comprises silicon (Si), silicon carbide (SiC), a composite of carbon and silicon (Si / C), and silicon oxide (SiO₂). q A method for manufacturing a negative electrode for a secondary battery comprising at least one of the following: , provided that 0.8≤q≤2.5). Claim 5 A method for manufacturing a negative electrode for a secondary battery according to claim 1, wherein the orientation index (OI) of the negative electrode slurry that has undergone the step of applying the magnetic field is in the range of 0.1 to 5: Claim 6 A method for manufacturing a negative electrode for a secondary battery according to claim 1, wherein the step of applying the magnetic field is performed by applying a magnetic field with a magnetic field strength in the range of 2,000G to 12,000G for 1 second to 30 seconds. Claim 7 A method for manufacturing a negative electrode for a secondary battery according to claim 1, wherein the porosity (%) of the negative electrode active material layer subjected to the rolling step is in the range of 25% to 35%. Claim 8 A method for manufacturing a negative electrode for a secondary battery according to claim 1, wherein the steps of applying a negative electrode slurry onto a current collector, applying a magnetic field, and drying are repeated in two process cycles, wherein in the first process cycle, a negative electrode slurry is applied to the top surface of the current collector to form a first negative electrode active material layer, and in the second process cycle, a negative electrode slurry is applied to the back surface of the current collector to form a second negative electrode active material layer. Claim 9 A method for manufacturing a negative electrode for a secondary battery according to claim 8, wherein in the first process cycle, the strength of the magnetic field applied in the step of applying the magnetic field is in the range of 2,000G to 9,000G, and in the second process cycle, the strength of the magnetic field applied in the step of applying the magnetic field is in the range of 2,500G to 9,500G. Claim 10 A method for manufacturing a negative electrode for a secondary battery according to claim 8, wherein the difference in the average orientation index (OI) between the first and second negative electrode active material layers is 1.5 or less. Claim 11 A negative electrode for a secondary battery comprising: a current collector; a first negative active material layer formed on one surface of the current collector; and a second negative active material layer formed on the opposite surface of the current collector, wherein the first and second negative active material layers have an orientation index (OI) according to the following Equation 1 in the range of 1 to 10, and the difference in the average orientation index (OI) of the first and second negative active material layers is 1.5 or less. [Equation 1] OI = I 004 / I 110 In the above Equation 1, I 004 represents the area of the peak indicating the (0,0,4) crystal plane of the carbon-based active material during X-ray diffraction (XRD) spectroscopic analysis of the cathode active material layer, and I 110 represents the area of the peak indicating the (1,1,0) crystal plane of the carbon-based active material during X-ray diffraction (XRD) spectroscopic analysis of the cathode active material layer. Claim 12 In claim 11, the negative electrode active material layer comprises natural graphite (GN) and artificial graphite (GA) as negative electrode active materials in a weight ratio of 60:40 to 40:60 (GA:GN) for a secondary battery negative electrode. Claim 13 delete Claim 14 A secondary battery comprising an electrode assembly having a structure in which a cathode, a positive electrode, and a separator are located between the cathode and the positive electrode according to claim 11.
Citation Information
Patent Citations
Solid electrolyte composition, solid electrolyte-containing sheet and all-solid-state secondary battery, and method for manufacturing the solid electrolyte-containing sheet and all-solid-state secondary battery
KR102288266B1
Positive electrode for nonaqueous electrolyte secondary battery
JP2010129481A
Negative electrode for non-aqueous electrolyte secondary battery and method for producing the same
KR1020120035213A
Lithium ion rechargeable battery and process for producing the lithium ion rechargeable battery
WO2008143027A1
